Metode Tafsir Tahlili,Ijmali, Muqaran dan Maudhu'i - Ilham Arifin Rambe; Netti Rosmawan Rambe; Farid Adnir (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study talks about four main ways of interpreting the Qur'an: tahlili, which is analytical; ijmali, which is global; muqaran, which is comparative; and maudhu'i, which is thematic. This study uses a library research method with a descriptive and qualitative analysis approach to explain what each tafsir method is, their features, how to apply them, and the pros and cons of each one. The results show that even though the four methods are different in how they approach things, their main idea is the same—that the mufassir is trying to explain the meaning of Qur'anic verses for themselves and for others. The Tahlili method is great for getting a deep understanding and is helpful for students studying Qur'anic science, but it takes more time and isn't the best choice for beginners. The ijmali method works well for people who are new to the topic or not experts, because it gives a clear and general overview.However, it doesn't go into much detail or analysis. The muqaran method offers detailed understanding by comparing different interpretations from various schools of thought, but it might be hard for new readers to follow. The Maudhu'i method offers a thorough understanding of themes that is very useful for dealing with current problems, but it doesn't give the full background of the whole verse. It is important for those studying the Qur'an to understand these four methods of interpretation so they can pick the one that fits their level of knowledge and helps them get the best possible understanding of the Qur'an.